2001
DOI: 10.1038/35104547
|View full text |Cite
|
Sign up to set email alerts
|

Female sticklebacks count alleles in a strategy of sexual selection explaining MHC polymorphism

Abstract: The origin and maintenance of polymorphism in major histocompatibility complex (MHC) genes in natural populations is still unresolved. Sexual selection, frequency-dependent selection by parasites and pathogens, and heterozygote advantage have been suggested to explain the maintenance of high allele diversity at MHC genes. Here we argue that there are two (non-exclusive) strategies for MHC-related sexual selection, representing solutions to two different problems: inbreeding avoidance and parasite resistance. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
442
8
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 408 publications
(466 citation statements)
references
References 23 publications
12
442
8
1
Order By: Relevance
“…The Atlantic cod genome has been shown to harbor 80-100 copies of MHC I (ref. 4), which is 15 times higher than the copy number determined to be optimal in the three-spined stickleback 14,17 . To investigate the evolutionary origin of the gadiform MHC I expansion and potentially detect other expansions, we estimated the MHC I copy numbers of the two peptide-binding lineages (U and Z) in the 66 sequenced species.…”
Section: Loss Of Mhc II Pathway Genesmentioning
confidence: 74%
See 1 more Smart Citation
“…The Atlantic cod genome has been shown to harbor 80-100 copies of MHC I (ref. 4), which is 15 times higher than the copy number determined to be optimal in the three-spined stickleback 14,17 . To investigate the evolutionary origin of the gadiform MHC I expansion and potentially detect other expansions, we estimated the MHC I copy numbers of the two peptide-binding lineages (U and Z) in the 66 sequenced species.…”
Section: Loss Of Mhc II Pathway Genesmentioning
confidence: 74%
“…Although an increase in the number of MHC genes facilitates pathogen detection, it will also decrease the number of circulating T cells [13][14][15][16] , resulting in an immune system that can detect a large number of pathogens at the expense of being less efficient in removing them. The evolution of MHC copy numbers is therefore likely driven toward intermediate optima determined by a tradeoff between detection and elimination of pathogens-as suggested by selection for 5-10 copies inferred in case studies of fish 17,18 and birds 19 .…”
mentioning
confidence: 99%
“…For example, olfactory cues may be used to assess the MHC composition of potential partners and, subsequently, to choose a mate (Potts et al 1991;Wedekind & Furi 1997;Landry et al 2001;Reusch et al 2001;Aeschlimann et al 2003). Despite popular belief to the contrary, olfactory cues can be important in birds (Ioale & Papi 1989;Clark et al 1993;Hagelin et al 2003) and smell could be used to assess the MHC of potential partners.…”
Section: Discussion (A) Mhc-based Mate Choicementioning
confidence: 99%
“…Various studies have provided evidence that MHCbased mate choice occurs in mammals and fishes (Yamazaki et al 1988;Potts et al 1991;Ober et al 1997;Wedekind & Furi 1997;Penn & Potts 1999;Reusch et al 2001;Aeschlimann et al 2003), though some other studies have found no such patterns (Hedrick & Black 1997;Paterson & Pemberton 1997;Wedekind et al 2004). Although birds have been used extensively for studies of sexual selection and mate choice, little work has focused on the role of the MHC (von Schantz et al , 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, hatchery rearing for compensatory purposes has created new demographic pressures on endangered wild populations of these fish. Some traits are artificially selected for in hatchery environment, like genes for pathogen resistance (reviewed by Fjaelstad et al 1993), for instance genes of the Major Histocomapatibility Complex (MHC) that confer resistence to disease in vertebrates (Reusch et al 2001). However, considering the fact that local populations contain long-term adapted genomes to local environments, gene flow between farmed and wild fishes is likely to erode local adaptation and possibly lead to their extinction (McGinnity et al 2003).…”
Section: Human Impact On Salmonid Ejaculate Allocation and Heritabilimentioning
confidence: 99%